PENGARUH PERBEDAAN UMPAN TERHADAP POLA TINGKAH LAKU MAKAN IKAN KERAPU MACAN (Ephinephelus fuscoguttatus) - Aristi Dian P Fitri; Ari Purbayanto (Institut Pertanian Bogor, 2009)
Study on fish behavior is necessary to establish knowledge on the use of bait effectiveness. The objective of the research was to analyze response and feeding behavior of grouper (Ephinephelus fuscoguttatus) on different chemical composition of bait. The research was conducted by laboratory experimental method. The fish used was 200 mm in total length. The baits used were shrimp (Metapenaeus elegans) and trash fish (Sardinella gibbosa). Data collection consist of response time and feeding behavior pattern of Ephinephelus fuscoguttatus on bait with soaking time of 1, 7, and 12 hours. Chemical composition of each bait consisting of proximate, amino acid, fatty acid, and ammonia were analyzed based on soaking time. Data was analyzed using t-student test. The results showed that response time of Ephinephelus fuscoguttatus to shrimp bait and fish was insignificantly difference (p > 0.05). The feeding response of Ephinephelus fuscoguttatus with soaking time difference of shrimp bait and trash fish during 1 and 7 hours was significantly difference (p < 0.01). The bait soaking time until 12 hours was insignificantly difference (p > 0.05). Longer bait soaking time (until 12 hours) would decrease bait chemical composition that influenced on decrease feeding response of Ephinephelus fuscoguttatus.Key words: baits, feeding habit, Ephinephelus fuscoguttatus.